Monitoring of the ground‐dwelling beetle community and forest floor environment in 22 temperate forests across Japan. Issue 5 (8th August 2016) - Niwa, Shigeru; Toyota, Ayu; Kishimoto, Toshio; Sasakawa, Kôji; Abe, Shin; Chishima, Takeshi; Higa, Motoki; Hiura, Tsutom; Homma, Kosuke; Hoshino, Daisuke; Ida, Hideyuki; Kamata, Naoto; et al.
Abstract: This data paper reports census data of ground‐dwelling beetle and other fauna of the forest floor environment; collections were made from a network of 22 forest sites in Japan. To our knowledge, this represents the largest dataset for long‐term monitoring of a ground‐dwelling beetle community and other taxa in a ground environment in forests, which covers a broad climatic range in the temperate zone and is freely available. The network forms part of the Monitoring Sites 1000 Project launched by the Ministry of the Environment, Japan. It covers subalpine, cool‐ and warm‐temperate and subtropical climatic zones and the four major forest types of Japan. Thirty‐three permanent plots usually 1 ha in size were established in old‐growth, secondary natural and a few plantation forests. Censuses of the ground‐dwelling beetle community were conducted using pitfall trapping and forest floor environment monitoring every year from 2004 to the present. During the initial 9 years of the census (2004–2012), 59, 762 beetle individuals (including 3182 larvae) of more than 314 species were recorded. This dataset includes taxonomy and biomass of each beetle individual and each taxonomic group of other invertebrates coincidently captured in pitfall trapping. The dataset also includes data related to ground coverage by forest floor vegetation, dry mass of the accumulated organic litter layer, and carbon and nitrogen contents and cellulose decomposition rate in organic layer and surface mineral soil. The data could be used to investigate geographical patterns and intra‐ and inter‐annual dynamics of individual body mass, populations and community structures of ground‐dwelling beetles, and their relationships with the forest floor environment. Furthermore, the data could be analyzed with other open datasets related to tree community dynamics and litter fall continuously measured in the same study plots. This dataset also provides information related to the distribution and average body mass of each beetle species.